Partial retirement and labor supply: Evidence from Swedish collective bargaining agreements - Emil Bustos (Research Institute of Industrial Economics (IFN), 2024)
Aging populations strain pension systems, prompting policymakers to introduce partial retirement schemes to incentivize workers to retire later. I study the impact of introducing partial retirement within collective bargaining agreements in Sweden's manufacturing sector in 2013. Merging collective bargaining data with administrative records, I employ a difference-in-differences methodology to analyze the labor market trajectories of eligible and ineligible cohorts around the introduction year. The results reveal a nuanced picture: while eligible workers are more likely to work and claim pension benefits simultaneously, this comes at the expense of a 10% decline in employment rates and a SEK 50,000 reduction in labor earnings. In summary, partial retirement fails to extend working lives, thus undermining its utility as a one-size-fits-all solution to the future of pension systems.
Keywords: D15; J26; J32; 330; Partial Retirement; Pension; Labor Supply